2019
DOI: 10.1021/acsinfecdis.9b00042
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Silkworm Cecropin B Antimicrobial Activity against Pseudomonas aeruginosa from Single Amino Acid Variation

Abstract: Pseudomonas aeruginosa is an opportunistic bacterial pathogen causing severe infections in hospitalized and immunosuppressed patients, particularly individuals affected by cystic fibrosis. Several clinically isolated P. aeruginosa strains were found to be resistant to three or more antimicrobial classes indicating the importance of identifying new antimicrobials active against this pathogen. Here, we characterized the antimicrobial activity and the action mechanisms against P. aeruginosa of two natural isoform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 49 publications
2
46
0
Order By: Relevance
“…It has been demonstrated that the antimicrobial activity of Cec AMPs relies on the structure they assume in the presence of bacterial cells. Circular dichroism analyses showed that in aqueous solution, Cecs have a random coiled structure but adopt α-helical conformations upon interaction with microbial membranes, where they exert a lytic effect [53,58,84,86]. Although some aspects remain unclear, it is currently accepted that Cec peptides do not interact with specific receptors but initially associate with the bacterial membrane along the axes of the α-helical domains parallel to the lipid bilayer surface.…”
Section: Cec Gene Expression and Mechanism Of Action Against Micromentioning
confidence: 99%
See 3 more Smart Citations
“…It has been demonstrated that the antimicrobial activity of Cec AMPs relies on the structure they assume in the presence of bacterial cells. Circular dichroism analyses showed that in aqueous solution, Cecs have a random coiled structure but adopt α-helical conformations upon interaction with microbial membranes, where they exert a lytic effect [53,58,84,86]. Although some aspects remain unclear, it is currently accepted that Cec peptides do not interact with specific receptors but initially associate with the bacterial membrane along the axes of the α-helical domains parallel to the lipid bilayer surface.…”
Section: Cec Gene Expression and Mechanism Of Action Against Micromentioning
confidence: 99%
“…Finally, in a study evaluating the interaction between different B. mori natural Cec B variants and live Gram-negative Pseudomonas aeruginosa , it was suggested that Cecs might first affect the outer bacterial membrane, enabling the translocation of the peptide to the inner membrane, resulting in the disorganization of both lipid bilayers [53].…”
Section: Cec Gene Expression and Mechanism Of Action Against Micromentioning
confidence: 99%
See 2 more Smart Citations
“…Murepavadin is a specific weapon against P. aeruginosa , which sets it apart from the large pipeline of natural and synthetic antimicrobial peptides that act against multiple taxa, including P. aeruginosa . Several novel peptides with broad antimicrobial activity—for example, DGL13K 49 , Mel4 50 , melimine 50 , cecropin B 51 , LBP-2 52, 53 , Pse-T2 54 , 6K-F17 55 , MDP1 56 , and MDP2 56 —have recently been described.…”
Section: Antibioticsmentioning
confidence: 99%